2021
DOI: 10.1101/2021.09.27.461935
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The activities of LRRK2 and GCase are positively correlated in clinical biospecimens and experimental models of Parkinson’s disease

Abstract: LRRK2 is a kinase involved in different cellular functions, including autophagy, endolysosomal pathways and vesicle trafficking. Mutations in LRRK2 cause autosomal dominant forms of Parkinson's disease (PD). Heterozygous mutations in GBA1, the gene encoding the lysosomal enzyme glucocerebrosidase (GCase), are the most common genetic risk factors for PD. Moreover, GCase function is altered in idiopathic PD and in other genetic forms of the disease. Recent work suggests that LRRK2 kinase activity can regulate GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…As the G2019S mutation causes an increase in LRRK2 kinase activity, the prediction from these studies would be that inhibition of LRRK2 kinase activity would result in an increase in GBA protein levels and a decrease in specific activity. In a recent work, Kedariti et al showed that pharmacological inhibition of G2019S LRRK2 in HEK293T cells caused a significant reduction in GCase activity when it was normalized by GBA levels, being consistent with the results in our study [16].…”
Section: Discussionsupporting
confidence: 93%
“…As the G2019S mutation causes an increase in LRRK2 kinase activity, the prediction from these studies would be that inhibition of LRRK2 kinase activity would result in an increase in GBA protein levels and a decrease in specific activity. In a recent work, Kedariti et al showed that pharmacological inhibition of G2019S LRRK2 in HEK293T cells caused a significant reduction in GCase activity when it was normalized by GBA levels, being consistent with the results in our study [16].…”
Section: Discussionsupporting
confidence: 93%
“…All participants provided written informed consent to take part in the study, and the study protocol was approved by the IRBs of both Columbia Univers0ity (CUIMC). PBMCs were isolated using standard protocols as previously described (83). Briefly, BD Vacutainer tubes (Sodium Heparin or Sodium Citrate) were used to collect whole blood from study participants.…”
Section: Peripheral Blood Mononuclear Cell (Pbmc) Isolation and Trans...mentioning
confidence: 99%
“…hESCs are pluripotent cells that have been derived from the inner cell mass of an early-stage embryo (Thomson et al, 1998) while iPSCs are generated from adult somatic cells, usually skin fibroblast cells, that are induced to pluripotency via a combination of four transcription factors (Takahashi and Yamanaka, 2006;Takahashi et al, 2007). Advances over the last decade or so, in defining differentiation conditions have made it possible to directly drive differentiation of human pluripotent cells to DA neurons and use these derived neurons to model PD in a dish (Yang et al, 2008;Chambers et al, 2009;Swistowski et al, 2010;Kriks et al, 2011;Gonzalez et al, 2013;Zhang et al, 2014;Singh et al, 2017;Barbuti et al, 2020;Kedariti et al, 2022;Stern et al, 2022). Multiple studies from different research laboratories have also shown that these derived neurons not only have cellular and biochemical characteristics very similar to the neurons developed in the human brain but also are functional when transplanted into animal models and thus, may have the potential to contribute to regenerative treatment options for the disease (Byers et al, 2011;Kriks et al, 2011;Doi et al, 2014;Grealish et al, 2014;Byers et al, 2015;Hoban et al, 2020;Behl et al, 2022).…”
Section: Introductionmentioning
confidence: 99%